MACRÓFITAS NÃO CONVENCIONAIS UTILIZADAS NA BIORREMEDIAÇÃO DE ZINCO - ALVARISTO, LUCAS RODRIGO NEVES (2020)
Phytoremediation is a low-cost process, considered green technology and provides a remediation of contaminated environments. Contamination of aquatic environments by metals is a worldwide problem. The metals are important sources of water contamination, as they are persistent in the environment and can accumulate in organisms along the food chains, causing problems in human health, animals, and plants. The objective of this work was to evaluate the capacity of zinc phytoremediation by Limnobium laevigatum and Phyllanthus fluitans through ecotoxicological tests. Because there is lack of information on aquatic plant cultivation methods in the laboratory and because they are non-conventional species, it was necessary to carry out initial tests. Those tests were used for evaluation of growth, adequate pH for development and physiological parameters evaluated by chlorophyll a fluorescence. The pH 6.0 was selected for the zinc test at concentrations of 0, 5, 10, 15, 20 and 25 ppm. After 7 days, the increase in fresh mass, relative leaf area and tolerance index of L. laevigatum roots showed a tendency to dosedependent reaction in both species. In relation to pigments, there was a reduction in the content of chlorophylls a, b and total, however, the levels of carotenoids remained stable. The evaluated fluorescence parameters indicated little metal influence on the efficiency of photosystem II (FO), non-photochemical energy dissipation (FM), on variable fluorescence (FV), as there were no significant reductions in these parameters. The photochemical efficiency of PSII (FV/FM) remained around 0.7 while the potential activity of PSII (FV/FO) indicated that there were photochemical losses in P. fluitans when compared to L. laevigatum. The cluster and main component analysis provided the differentiation of species and treatments, as well as the selection of physiological markers of the species tested against zinc. The data obtained indicate that the tested species suggest the ability of zinc phytoremediation in contaminated effluents, considering that they obtained good results even in high concentrations of the metal.